Catharine Macaulay and Mercy Otis Warren : the revolutionary Atlantic and the politics of gender - Davies, Kate, 1973- (OUP E-Books., 2005)
Catharine Macaulay and Mercy Otis Warren were radical friends in a revolutionary era. They produced definitive histories of the English Civil War and the American Revolution, attacked the British government and the United States federal constitution, and instigated a debate on women's rights which inspired Mary Wollstonecraft and other feminists. Setting Warren and Macaulay's lives and writing in the context of the revolutionary Atlantic, this is the first book to consider one of. the eighteenth century's most important political friendships. - ;Catharine Macaulay and Mercy Otis Warren were ra.